External Beam Therapy in a Four-Field Box Technique with Paclitaxel versus a Two-Field Technique with Cisplatin in Locally Advanced Carcinoma Cervix: A Phase II Monocentric Trial. (31st December 2012) - Narayanan, Vijayakumar; Bista, Bibek; Sharma, Samir
Abstract : Introduction . External beam pelvic radiotherapy with cisplatin and brachytherapy is the standard of care for patients with advanced cervical malignancy. This study was aimed at evaluating the toxicity of a two-field radiotherapy with cisplatin and brachytherapy compared to a four-field box technique with paclitaxel and brachytherapy for stages IIB/IIIB cervical cancer. The differences in response to the overall treatment were also examined. Methods . 35 patients were enrolled in this phase II prospective randomized trial conducted from February 2006 to February 2007. In arm I, up to 40 Gy in 20 fractions followed by 10 Gy in 5 fractions in split field with cisplatin 40 mg/M 2 and, in arm II, 50 Gy in 25 fractions with paclitaxel 50 mg/M 2 were given. Results . Toxicity in genitourinary, lower gastrointestinal, and hematological tissues was significantly higher in arm I. The duration of concurrent chemoradiotherapy in either arm was similar. The overall treatment time was less in arm II. No statistically significant difference in the objective response was observed between arms. Conclusion . Two-field radiotherapy with cisplatin is a tolerable regime but more toxic than four-field box radiotherapy with paclitaxel. The major setbacks are that a radiotherapy technique as well as chemotherapy is different; hence, toxicity and outcome of treatment should be viewed as a collective response of the whole treatment regimen and the small sample size.